Computed microtomography study of untreated, shaped and filled mesiobuccal canals of maxillary first molars. (16th August 2018) - Angerame, Daniele; De Biasi, Matteo; Brun, Francesco; Turco, Gianluca; Franco, Vittorio
Abstract: This study assessed the effectiveness of modern endodontic shaping and filling procedures on mesiobuccal roots of maxillary molars with two canals. The canals of 20 mesiobuccal roots were treated with Mtwo rotary files, passive ultrasonic irrigation and Guttafusion obturators. X‐ray computed microtomography analysis was carried out prior to treatment, after canal shaping and after canal filling to determine the alterations of the canal volume before and after the instrumentation, the volume of the hard tissue debris, and percentage of the volume occupied by filling materials. The shaping instruments and filling materials reached only partially the endodontic space of the second mesiobuccal canal and the accessory endodontic structures. Canal irregularities, ramifications, and interconnections were accumulation sites of hard tissue debris. This study demonstrated that rotary files, passive ultrasonic irrigation and carrier‐based filling systems could be partially effective for the treatment of the mesiobuccal canals and their accessory endodontic structures.